Changes of Volume Parameters in the Treatment of Graves Ophthalmopathy by Endoscopic Transethmoidal Decompression of the Orbital Inner Wall Combined with Fat Decompression. (24th August 2022) - Fu, Weina
Abstract : Objective . To observe the orbital volume changes and the analysis of surgical effect of Graves orbitopathy (GO) after endoscopic medial wall decompression combined with muscle cone fat. Methods . Twenty-two patients (30 eyes) with Graves orbital disease who visited the Department of Ophthalmology of Ningbo Medical Center from December 2019 to September 2021 were retrospectively collected. All patients were diagnosed as nonorganic active stage before operation, and all of them received endoscopic transethmoidal decompression of the medial orbital wall combined with intramuscular orbital fat decompression due to decreased vision, visual field defect or color vision disorder, and concomitant proptosis. Regular follow-up after operation. The curative effect is judged according to the degree of improvement of visual acuity, color vision, degree of correction of exophthalmos, diplopia, and other complications at 9 months after operation. Orbital CT combined with computer aided measurement software (Mimics 21) was used to measure the changes of orbital volume before and after exophthalmos surgery. The relationship between the value and eyeball regression is analyzed. Results . Preoperative exophthalmos ranged from 17.4 mm to 27.6 mm, with an average of (22.08 ± 2.86 ) mm. The postoperative exophthalmos was 14-25 mm, with an average of (19.52 ± 3.10 ) mm. Among them, 7 eyes (23.3%) had exophthalmos regression less than 1 mm, 6 eyes (20%) had a regression of 1-2 mm, 7 eyes (23.3%) had a regression of 2-3 mm, 5 eyes (16.7%) had a regression of 3-4 mm, and 5 eyes (16.7%) had a regression of 4-5.3 mm. The exophthalmos after operation was significantly lower than that before operation, and the difference was statistically significant (t = 9.909, P < 0.05 ). The preoperative orbital volume was 18.6 cm 3 -25.3 cm 3 with an average of (22.39 ± 1.91 ) cm 3 . The postoperative orbital volume was 19.8 cm 3 -26.6 cm 3, with an average of (23.89 ± 1.90 ) cm 3 .The orbital volume change range is 0.1 cm 3 -3.8 cm 3, and the average orbital volume change is (1.51 ± 1.00 ) cm 3 . Compared with preoperative orbital volume, the difference was statistically significant (t = − 8.074, P < 0.05 ). Conclusion . Endoscopic decompression of the medial orbital wall through the ethmoid approach combined with decompression of the orbital fat within the muscle cone can effectively correct the exophthalmos while decompressing the orbital apex, and it is minimally invasive and has no facial scars. It has the advantages of extremely low incidence of postoperative diplopia and eye shift. There is a significant correlation between orbital volume changes and the regression of exophthalmos, which can provide reference for clinical guidance of surgical methods and prediction of surgical results.